Assessment of Development - Laak, Jan J. F. ter (1999)
It is argued that developmental psychology is the "third discipline of scientific psychology" , emphasizing the formal aspect of behavioral continuity/change. Constructs elaborating this aspect are semantical and not empty mathematical models or fuzzy common sense concepts. Assessment is comprehensively describcd as a matrix of four components (test theory, constructs, tests, diagnostica! proces) by three levels (common sense, scientific constructs, mathematical models). Developmental psychology and assessment are confronted to conquer and extend the meaning of continuity/change, as in "convergent" and "discriminant" construct validation. Test theory, tests and the diagnostica! proces respective! y offer models, instruments and a program for assessing behavior.